Germination test and ornamental potential of different basil cultivars (Ocimum spp.) - França,Matheus Filipe de Moraes Sousa (2017)
ABSTRACT Basil (Ocimum spp.) is an essential oil producing plant and it is used as a condiment for diferent foods, besides serving as raw material for medicinal purposes. This crop has also been showing great importance as an ornamental plant in recent years. However, basil lacks studies concerning its different usages with special regards to its ornamental potential. Therefore, this study aimed at evaluating the vegetative development and the ornamental potential of the basil cultivars ‘Grecco a Palla’ (O. minimum), ‘Alfavaca Basilicão Vermelho’ (O. basilicum), and ‘Thai Basil’ (O. basilicum), under protected cultivation. The following characteristics were evaluated: germination percentage, germination speed index, plant canopy diameter (cm), leaf and inflorescence length (cm), plant height (cm), and fresh and dry leaf mass (g). The ornamental potential was estimated based on visual evaluations of plant canopy volume; leaf shape, texture, size, and color; stem and flower color; and number of days to flowering. Cultivar ‘Thai Basil’ presented the highest leaf dry mass and ‘Grecco a Palla’ showed the highest germination speed index and seed germination percentage. All cultivars bloomed within 60 days after planting and exhibited color and brightness variability, which are desirable traits for a landscape composition. ‘Grecco a Palla’ stood out for its short and compact inflorescences, dwarf size and globular shape when grown as a potted plant. The studied cultivars demonstrated favorable characteristics for ornamental usage based on visual assessments.